OPINION OF INTERNAL PARTICIPANTS ON INTERNAL CONSTRANTS OF DISKOMINFO BANGKA BARAT IN SUBMITTING INFORMATION THROUGH THE NEWS - Tri Oktaviani; Sepriadi Saputra (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research journal is entitled